Biodegradasi Senyawa Hidrokarbon Oleh Strain Bacillus cereus(VIC) Pada Kondisi Salinitas Yang Berbeda - Reza Auliarahman Bhaktinagara; Agung Suprihadi; Budi Raharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Bacillus cereus has been noted as hydrocarbonoclastic microbe that has ability to degrade hydrocarbons in non-saline conditions and some often to be found on high salinity environtment conditions. The purpose of this research is to determine the ability of strains Bacillus cereus (VIC) were isolated from non-saline environment to degrade hydrocarbons in crude oil on the different salinity condition. Bacillus cereus (VIC) was inoculated on the medium that has contaminated by crude oil with salinity level of 0,3 , 9,4 , dan 19,6 and incubated for 15 days. Determination of microbial growth is by using Total Plate Count (TPC) method along with determination of Total Petroleum Hydrocarbon (TPH) percentage using gravimetry method for every 5 day. The determination of microbial growth showed that Bacillus cereus (VIC) has the tolerancefor salinity level up to 19,6 because it is able to grow to a density of 6.9 x 106 CFU/ml on the 15th day. Bacillus cereus (VIC) is also able to degrades hydrocarbons on crude oil pollutants that indicated from degradation of TPH percentage in the medium up to 21% during 15 days incubation period on the medium with salinity level of 19,6 . Biodegradation using Bacillus cereus (VIC) can increase TPH degradation on the medium up to 19,8% than TPH degradation because of weathering. Keywords: Biodegradation, Bacillus cereus(VIC), Total Petroleum Hydrocarbon (TPH), Salinity.